V. I. VERNADSKY’S DOCTRINE ON NOOSPHERE AND JUSTICE CONCEPT IN CONTEXT OF TECHNO-GENESIS PROBLEMS OF CONTEMPORANEITY - N. I. Mushinskij (Наука и техника)
A noosphere conception reflects actual problems of a technocratic society in the current context. A new interpretation of social justice has an important significance in the ecological heritage of V. I. Vernadsky. Application of the noosphere theory, revelation of innovational justice aspects with the help of the theory permit successfully to solve techno-genesis problems aggravated at the beginning of the third millennium.